1991
DOI: 10.1164/ajrccm/143.3.640
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Mucus Hypersecretion in Acute Quadriplegia: Macromolecular Yields and Glycoconjugate Composition

Abstract: In acute quadriplegia we have noted that about one in five patients develops unexplained production of markedly excessive and tenacious bronchial mucus. Spontaneous recovery from mucus hypersecretion usually occurs within weeks to months. Mucus samples collected from 12 patients have been found to be abnormal. Macromolecular contents of single aspirates yielded as much as 500 mg. Analytical ultracentrifuge analysis showed the mucus to contain considerable epithelial glycoprotein (GP) of typical buoyant density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 8 publications
0
27
1
2
Order By: Relevance
“…In some of the SCL patients, V T decreased gradually during the manoeuvre, indicating that IR-PEP acted restrictively on respiratory function. Earlier studies by Bhaskar et al 7 and Liaw et al 21 have shown positive effects on static lung volumes and maximum inspiratory pressure after respiratory training with resistive breathing during inspiration only, which is a different method from IR-PEP. Future studies should also involve this type of training.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In some of the SCL patients, V T decreased gradually during the manoeuvre, indicating that IR-PEP acted restrictively on respiratory function. Earlier studies by Bhaskar et al 7 and Liaw et al 21 have shown positive effects on static lung volumes and maximum inspiratory pressure after respiratory training with resistive breathing during inspiration only, which is a different method from IR-PEP. Future studies should also involve this type of training.…”
Section: Discussionmentioning
confidence: 98%
“…6 In complete lesions above the Th6 level, the autonomic nervous system is injured, and bronchial hypersecretions occur, which further aggravates problems regarding secretions. 7 To prevent pulmonary complications such as atelectasis and pneumonia, intensive respiratory training is given routinely during the first weeks after the injury.…”
Section: Introductionmentioning
confidence: 99%
“…1 Loss of innervations of abdominal and intercostal respiratory muscles in these patients causes a reduced ability to cough, hypersecretions, accumulation of secretion in the airways, which in combination with immobilisation, increases the risk of respiratory complications. 2,3 Deep breathing exercises and resistive expiratory breathing are commonly practised to prevent respiratory complications in the acute phase of SCL since they are thought to enhance mucus clearance. Although scientific evidence for such effects is essentially lacking, 4 this does not necessarily imply that such effects do not exist.…”
Section: Introductionmentioning
confidence: 99%
“…The lungs in individuals with acute complete cervical SCI have decreased lung expansion, a highly impaired cough due to the weakness of expiratory muscles, impairment of the elastic recoil of the diaphragm and lung, increased secretion production due to an unopposed parasympathetic stimulation, and decreased surfactant production. 6,7 Therefore, interventions to aid secretion mobilization are crucial in preventing mucus plugging, atelectasis, pneumonia, and ventilatory failure following injury. Because the cough flow and effectiveness are greatly reduced with a cervical SCI, the ability to clear secretions is profoundly affected.…”
mentioning
confidence: 99%